2016
DOI: 10.1063/1.4943858
|View full text |Cite
|
Sign up to set email alerts
|

Time of flight spectrometer for background-free positron annihilation induced Auger electron spectroscopy

Abstract: We describe a novel spectrometer designed for positron annihilation induced Auger electron spectroscopy employing a time-of-flight spectrometer. The spectrometer's new configuration enables us to implant monoenergetic positrons with kinetic energies as low as 1.5 eV on the sample while simultaneously allowing for the detection of electrons emitted from the sample surface at kinetic energies ranging from ∼500 eV to 0 eV. The spectrometer's unique characteristics made it possible to perform (a) first experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The central obstacle for the direct measurement of the Auger electron spectrum produced by the valence hole decay has been the large secondary background in the low-energy regime, produced by the energetic electron or photon beams used to create the initial hole. Recent measurements in our laboratory9 have shown that it is possible to obtain Auger spectra that are completely free of such secondary electron background by utilizing a positron beam with an incident kinetic energy below ∼ 2 eV (ref. 10), the threshold for impact induced secondary electron emission.…”
mentioning
confidence: 99%
“…The central obstacle for the direct measurement of the Auger electron spectrum produced by the valence hole decay has been the large secondary background in the low-energy regime, produced by the energetic electron or photon beams used to create the initial hole. Recent measurements in our laboratory9 have shown that it is possible to obtain Auger spectra that are completely free of such secondary electron background by utilizing a positron beam with an incident kinetic energy below ∼ 2 eV (ref. 10), the threshold for impact induced secondary electron emission.…”
mentioning
confidence: 99%
“…The system is comprised of three parts: a positron beam with magnetic transport, a ToF energy spectrometer, and a sample preparation chamber. A more complete description of the system and its capabilities is provided in reference 37 . Positrons from a 22 Na source are moderated using a thin tungsten foil in transmission geometry before being magnetically guided to the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The ToF-PAES spectrometer at the University of Texas at Arlington (UTA) has been described in detail elsewhere [2]. Briefly stated, positrons from a 22 Na source are first moderated using a thin tungsten foil in transmission geometry before being magnetically guided to the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…The surface selectivity of PAES stems from the fact that the positron wave function in the surface state decays rapidly below the top-most atomic layer [1]. In PAES, positron beam energies well below the electron work function can be used to initiate the Auger process allowing for the complete elimination of the obscuring secondary electron background found in other similar techniques [2]. Experimental determination of the background-free, spectra of electrons emitted as a result of Auger transitions, down to 0 eV, is important for unravelling the complex, correlated Auger decay pathways of core and deep valence holes [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%